Onset and dose-related efficacy of house dust mite sublingual immunotherapy tablets in an environmental exposure chamber - Nolte, Hendrik; Maloney, Jennifer; Nelson, Harold S.; Bernstein, David I.; Lu, Susan; Li, Ziliang; Kaur, Amarjot; Zieglmayer, Petra; Zieglmayer, René; Lemell, Patrick; Horak, Friedrich (Journal of allergy and clinical immunology, 2015)
The magnitude of effect of sublingual immunotherapy for house dust mite (HDM)–induced allergic rhinitis with or without conjunctivitis is uncertain, partly because there are few well-controlled trials with well-defined doses. We sought to determine the dose-related efficacy and onset of action of the HDM sublingual immunotherapy tablet MK-8237 (Merck/ALK-Abelló) using the Vienna Challenge Chamber. In this randomized, double-blind, single-site trial, adults with HDM-induced allergic rhinitis with or without conjunctivitis and with or without asthma (n = 124) received 12 developmental units (DU) of MK-8237, 6 DU of MK-8237, or placebo daily for 24 weeks. Subjects underwent 6-hour exposure challenges at screening and weeks 8, 16, and 24. The total nasal symptom score (TNSS) during chamber challenge at week 24 was the primary end point. The TNSS was the sum of 4 nasal symptom scores (maximum = 12). Total ocular symptom scores (TOSSs; 2 symptoms; maximum = 6) and total symptom scores (TSSs; TSS = TNSS plus TOSS; maximum = 18) were secondary end points. Dose- and time-dependent improvements with MK-8237 versus placebo were observed. At week 24, TNSS improvement relative to placebo was 48.6% (95% CI, 35.3% to 60.2%) with 12 DU of MK-8237 and 26.6% (95% CI, 11.2% to 39.6%) with 6 DU of MK-8237. Statistically significant improvements for TNSSs were also observed at weeks 8 (12 DU of MK-8237) and 16 (6 and 12 DU of MK-8237) and for TOSSs and TSSs by both doses at week 24. MK-8237 was well tolerated. No investigator-assessed anaphylactic allergic reactions or reactions requiring epinephrine were observed. MK-8237, 12 DU, reduced nasal and ocular symptoms and exceeded World Allergy Organization–established clinical efficacy criteria (≥20% improvement vs placebo). The onset of action for 12 DU of MK-8237 was week 8. MK-8237, 12 DU, is appropriate for further evaluation to determine the magnitude of effect in an uncontrolled allergen exposure environment.